Evolution of the Minangkabau Inheritance System and its Relevance to Gender Justice in Islamic Law - Nelna Saprina; Yulia Rahmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The inheritance system in Minangkabau, known for its matrilineal lineage, offers a unique perspective on property distribution, especially when contrasted with the patrilineal structure of Islamic inheritance law. This research delves into the historical and cultural evolution of the Minangkabau inheritance system, examining how it has adapted over time due to various social, legal, and religious influences. While Minangkabau customary law (adat) traditionally prioritizes female heirs, particularly through maternal lines, Islamic inheritance law advocates a more balanced approach, emphasizing the rights of both male and female heirs based on predetermined shares. The contrast between these two systems raises important questions about gender justice and the equitable distribution of wealth. Through a detailed exploration of Minangkabau customs and Islamic jurisprudence, this study investigates how these systems have coexisted and the efforts made by scholars and legal authorities to reconcile the differences. A significant focus is placed on the role of reformist thinkers within the Minangkabau community, who have sought to align local practices with the broader principles of Islamic inheritance law while preserving cultural identity. The research also examines the practical implications of these reform efforts, particularly in light of the evolving role of women in Minangkabau society and the growing calls for gender equality. The findings offer valuable insights into the potential for developing an inheritance model that respects both cultural traditions and Islamic values of justice, ultimately contributing to a broader discourse on gender equity in inheritance laws across diverse Muslim societies.